2021
DOI: 10.1007/s11606-021-07143-3
|View full text |Cite
|
Sign up to set email alerts
|

“They Wanted to Talk to a ‘Real Doctor’”: Predictors, Perpetrators, and Experiences of Racial and Ethnic Discrimination Among Healthcare Workers

Abstract: Background Racial and ethnic diversity of healthcare workers have benefits on team functioning and patient care. However, a significant barrier to retaining diverse providers is discrimination. Objective To assess the predictors, perpetrators, and narratives of racial discrimination among healthcare workers. Design Survey study. Participants Healthcare workers employed at academic hospitals. Main Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Other studies have also described the importance of considering multiple social identities to understand experiences of discrimination faced by women HCWs [ 39 , 40 ]. For example, another study that utilized quantitative and qualitative methods to explore racial discrimination among HCWs identified that experiences of racial and ethnic discrimination were most common among HCWs of color, and that these experiences were interpreted in light of intersecting identities, namely gender, race, and ethnicity [ 41 ]. Another study including medical students found that microaggressions were most frequent among Black women, compared with Black men and White women [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also described the importance of considering multiple social identities to understand experiences of discrimination faced by women HCWs [ 39 , 40 ]. For example, another study that utilized quantitative and qualitative methods to explore racial discrimination among HCWs identified that experiences of racial and ethnic discrimination were most common among HCWs of color, and that these experiences were interpreted in light of intersecting identities, namely gender, race, and ethnicity [ 41 ]. Another study including medical students found that microaggressions were most frequent among Black women, compared with Black men and White women [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination has been linked to poor health care delivery due to both patient and physician bias. 27,28 It is noted that some individuals may avoid seeing a physician entirely out of fear of discrimination. By alleviating the occurrence of microaggressions and correctly addressing them, HCPs can conduct high-quality care and therefore be more comforting to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown evidence of negative racialized experiences toward healthcare workers of color, which also has been linked to turnover decisions. For example, Hennein et al [ 10 ] surveyed 997 healthcare workers within academic hospitals to investigate the predictors, perpetrators, and nature of racialized encounters of workers of color. In the findings, 85% of the healthcare workers of color reported racialized experiences ranging from structural racism to interpersonal racism with their co-workers, supervisors, teachers, and patients.…”
Section: Social Backgroundmentioning
confidence: 99%
“…The literature has noted that inequities in healthcare systems have historical and contemporary roots in structural racism-cultural, societal, and organizational ideas and practices that are rooted in white supremacy [6][7][8]74]. Accordingly, the pervasive nature of structural racism in society, within which healthcare organizations are nested, severely undermines healthcare organizations' ability to actualize favorable gains through a diverse workforce when filling the gaps in their diversity and inclusion efforts [5,9,10]. Therefore, without an explicit focus on structural racism as a critical mechanism, our efforts to increase diversity and inclusion and eliminate health disparities have limited effects [11][12][13].…”
Section: Introductionmentioning
confidence: 99%